(untitled) (Challenges of the Future, 2023)
Research Question (RQ): How do the nurses master to work with patients with disabilities according to the knowledge they gain during formal and informal education? Purpose: Special needs of people with disabilities are an essential part of life. Persons with disabilities face numerous obstacles, therefore the attitude towards them is of great importance. The awareness of the significance of health literacy gives healthcare workers an opportunity to support patients and their families to surmount obstacles in the areas of health and welfare. The purpose of the research was to establish the amount of knowledge on working with patients with disabilities gained by nurses during their formal education, to establish their need to acquire additional knowledge, to establish the impact of their personal experiences on their point of view and attitude towards patients with disabilities and to determine what kind of experiences they have with relatives of patients with disabilities. Method: A qualitative research design was employed; data were collected with a survey. Data were collected with a structured questionnaire. For the interpretation of the data and the text written by respondents, a multi-phase approach of qualitative context text analysis was used. Context analysis of respondents’ answers yielded three main topics: (1) experiences on nursing patients with disabilities, (2) experiences with the relatives of patients with disabilities, and (3) the importance of knowledge on working with patients with disabilities. Collected data were coded and the interpretation of findings was made. Results: Our results revealed that nurses require formal education in the area of disabilities in their undergraduate and postgraduate curricula. They gain knowledge for working with patients with disabilities during the working process and by attending additional training and education. Nurses have both personal and professional experiences in the area and describe their relations with patients with disabilities and their relatives positively. Organization: The research was focused on the health literacy of nurses and patients with disabilities. The focus research primarily addresses the importance of health institutions and their workforce, which are required to ensure the safe and inclusive environment for vulnerable groups (in our case patients with disabilities). Society: Nursing has a long and important history of adjusting to changes in the society and its health needs and responds to demands of the society. Nurses play an important role in health care, so the necessary changes need to start with them. Nurses have an impact at personal and individual level and at organizational level. They are the most important when it comes down to promotion of health literacy as they are the ones working closest to patients and have contacts with patients on daily bases. Originality: The originality of the article can be seen in the study of a very current social issue, which affects the so far under-researched health literacy of nurses and patients with disabilities in Slovenia. The research is the first one of the kind in Slovenia. Limitations / further research: First, the number of respondents was too low. Second, this was the first research of this kind in Slovenia, so there are no other Slovene research data to compare our results with. Third, the instrument was made for the purpose of the research as the foreign instrument was out-of-date and unsuitable. The research also gives an idea for further research in the area as it is an important part of work of nurses.